Interannual variability of the upper ocean carbon cycle in the northeast Atlantic Ocean - González-Dávila, Melchor; Santana-Casiano, J. Magdalena; González-Dávila, Enrique F. (Geophysical Research Letters, 2007)
Surface waters in the subtropical gyres have persistently absorbed anthropogenic CO2 at a rate such that their inorganic carbon concentrations have shown a clear upward trend. We report a 10‐year time series of upper‐ocean inorganic carbon observations from the northeastern subtropical Atlantic at ESTOC which indicates significant variability in the inorganic carbon fluxes produced by variations in the Winter mixed‐layer depths, induced by sea surface temperature anomalies. This variability reflects fluctuations relating to the NAO for both sites of the sub‐tropical gyre, with the Eastern part showing a closer correlation with a 3‐year NAO delay. The response to interannual variations in the meteorological forcing to the extra‐tropical carbon cycle can be predicted to clarify effects on future climate change. 2,744 Q1 SCIE